2020
DOI: 10.1038/s41598-020-75930-9
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus casei extracellular vesicles stimulate EGFR pathway likely due to the presence of proteins P40 and P75 bound to their surface

Abstract: In the complex interplay of beneficial bacteria with the host, there are few examples of bacterial metabolites and effector molecules that have been consistently identified. Protective effects on the intestinal epithelium have been ascribed to P40 and P75, two well characterized cell wall muramidases, present in the culture supernatant of strains belonging to the taxon Lactobacillus casei/paracasei/rhamnosus. This work reports that Lactobacillus casei BL23 extracellular vesicles (BL23 EVs) have a small size (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 66 publications
3
34
0
Order By: Relevance
“…At the same time, L. rhamnosus EVs had the same effect in an in vivo model of dextran sulfate sodium-induced colitis in mice ( Tong et al, 2021 ). On the other hand, EVs from E. coli and L. casei increased NF-κB levels per se in Caco-2 and HT-29 cell lines ( Cañas et al, 2018 ; Bäuerl et al, 2020 ). This opposite modulation of NFκB levels, in the presence or absence of LPS, was also observed for pro-inflammatory cytokines like IL-8 in both Caco-2 and HT-29 cell lines, and in ex vivo human colonic explant ( Fábrega et al, 2016 ; Choi et al, 2020 ; Vargoorani et al, 2020 ).…”
Section: Extracellular Vesicles From Probiotic Bacteria and Infectiou...mentioning
confidence: 99%
See 3 more Smart Citations
“…At the same time, L. rhamnosus EVs had the same effect in an in vivo model of dextran sulfate sodium-induced colitis in mice ( Tong et al, 2021 ). On the other hand, EVs from E. coli and L. casei increased NF-κB levels per se in Caco-2 and HT-29 cell lines ( Cañas et al, 2018 ; Bäuerl et al, 2020 ). This opposite modulation of NFκB levels, in the presence or absence of LPS, was also observed for pro-inflammatory cytokines like IL-8 in both Caco-2 and HT-29 cell lines, and in ex vivo human colonic explant ( Fábrega et al, 2016 ; Choi et al, 2020 ; Vargoorani et al, 2020 ).…”
Section: Extracellular Vesicles From Probiotic Bacteria and Infectiou...mentioning
confidence: 99%
“…In vitro and in vivo experiments with intestinal epithelial cells have demonstrated that EVs released by E. coli , L. casei , L. paracasei , P. freudenreichii , and L. rhamnosus can modulate NFκB levels ( Cañas et al, 2018 ; Bäuerl et al, 2020 ; Choi et al, 2020 ; Vargoorani et al, 2020 ; Tong et al, 2021 ). NF-κB is a family of transcription factors and has an essential role in a variety of aspects related with human health including the development of both innate and adaptive immunity.…”
Section: Extracellular Vesicles From Probiotic Bacteria and Infectiou...mentioning
confidence: 99%
See 2 more Smart Citations
“…Vitro research results demonstrate that M3 receptor-induced activation of p38 MAPK might maintain epithelial barrier function by downregulating TNF-α signaling and activation of Epidermal growth factor receptors (EGFR) instead of H1 (Uwada et al, 2017). Both P40 and P75 proteins were shown to show anti-apoptotic features containing EGFR phosphorylation and, in the case of P40, preventing the intestinal epithelium from triggered inflammation in a vitro model (Bauerl et al, 2020) (Figure 4).…”
Section: Epidermal Growth Factor Receptorsmentioning
confidence: 99%